(untitled) (Biological Sciences - PJSIR, 2020)
In this study, we investigated various physico-chemical properties of wheat and evaluated their correlation with cookie attributes. Results showed that damaged starch in wheat varieties ranged from 6.28 to 10.97%. SDS-sed. and AWRC values were recorded as 18.20-30.50 mL and 43.91-66.85%, respectively. WSRC, SOCSRC, SUCSRC and LASRC values varied over a wide range as 50.83-69.64%, 56.66-82.03%, 75.79-106.97% and 79.43-121.20%, respectively. Physical analyses of cookies made with wheat varieties indicated 25.20-26.60 cm width, 5.80-6.40 cm thickness and 39.38-45.86 spread factor and 2.17-3.91 kg hardness. Important correlations were reported between water absorption and SDS sedimentation (r= 0.912*). Likewise, a positive relationship was found between damaged starch and SUCSRC (r= 0.985**).Spread factor was found to be negatively correlated to ash (r= -0.977**), protein(r= -0.892*), SOCSRC (r= -0.952*), WSRC (r= -0.892*) and hardness (r= -0.990**).Correlation studies indicated that physico-chemical characteristics of flour are imperative in the evaluation of cookie making quality.